ANALYSIS OF AWARENESS OF THE POSSIBILITIES OF IMPLEMENTING PERSONALIZED MEDICINE AMONG DOCTORS IN UKRAINE: NATIONAL SURVEY - Liudmylа О. Turova; Tetiana A. Vezhnovets; Valeriia Y. Kantsypa (Клінічна та профілактична медицина)
Aim. This study aims to assess the awareness of Ukrainian medical practitioners about personalized medicine, evaluate their readiness to adopt such approaches in clinical practice, and identify barriers that may hinder its implementation.